Dialektika AI dan Musik- Keresahan Estetis Komposer dan Tuntutan Adaptasi Profesional - Dominikus Raharja (Pantarei, 2026)
Abstract Artificial intelligence (AI) technology has profoundly influenced the music industry, particularly with the emergence of generative platforms like Suno AI, which enable the instant creation of songs. The result is a new dialectic between humans and machines. This phenomenon raises concerns among composers about professionalism and aesthetics while simultaneously opening new opportunities for creativity. Previous studies have focused more on public perception and technical aspects, while research on the composer's position from philosophical and hermeneutic perspectives remains limited. As a method for interpreting the meaning of music originating from human-machine interaction, this article employs a music philosophy approach grounded in hermeneutics and the frameworks of ontology, epistemology, and axiology. The analysis results show that the transformation of musical aesthetic values necessitates a shift in the composer's role from a sole creator to a curator and conceptor. Epistemologically, artificial intelligence blurs the distinction between music as an algorithmic product and as a human expression. Axiologically, there is a tension between musical knowledge based on tradition, intuition, and experience and AI knowledge derived from data and statistics. Approached through a hermeneutic framework, this dialectic can be understood as a multi-layered process of interpretation. In this process, composers do not merely compete with machines; they also reinterpret the role and meaning of music within the digital environment. The key finding of this article is that artificial intelligence is not only a threat but also aids in the redefinition of musical professionalism in the contemporary era. The discovery of a new philosophical synthesis is the novelty (contribution) of this research. In this synthesis, the hermeneutic collaboration between humans and artificial intelligence is posited as a more relevant alternative creative model for the dynamics of the modern music industry.